Shortcuts to adiabaticity by counterdiabatic driving for trapped-ion displacement in phase space - Shuoming An (Nature Portfolio, 2016)
The application of adiabatic protocols in quantum technologies is limited due to the detrimental action of decoherence. Here the authors demonstrate a shortcut to adiabaticity via counterdiabatic driving in a trapped ion system.